2021
DOI: 10.3389/fphar.2021.674416
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Mechanism of Indigo Naturalis in the Treatment of Ulcerative Colitis Based on TLR4/MyD88/NF-κB Signaling Pathway and Gut Microbiota

Abstract: Background: Clinical trials have proven that indigo naturalis is a candidate drug for treating ulcerative colitis (UC), but its therapeutic mechanism is still unclear.Purpose: This study aimed to evaluate the protective effect and mechanism of indigo naturalis to treat mice with dextran sulfate sodium (DSS)-induced UC.Methods: DSS-induced UC mice were treated with indigo naturalis (200 mg/kg), indigo (4.76 mg/kg), and indirubin (0.78 mg/kg) for 1 week. The anti-UC mechanism of indigo naturalis was studied by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…Eriodictyol treatment alleviates TNBS-induced colon inflammation and intestinal tissue damage in rats by inactivating the TLR4/NF-κB signaling [61]. Indigo and indirubin repair intestinal mucosa, reduce inflammation, regulate intestinal flora, and ameliorate physiological symptoms of DSSinduced colitis in mice via repressing TLR4/MyD88/NF-κB signal transduction [62]. In our study, DSS exposure elevated the levels of TLR4, MyD88, p-p65 and p-IκBα in colon tissues.…”
Section: Discussionsupporting
confidence: 54%
“…Eriodictyol treatment alleviates TNBS-induced colon inflammation and intestinal tissue damage in rats by inactivating the TLR4/NF-κB signaling [61]. Indigo and indirubin repair intestinal mucosa, reduce inflammation, regulate intestinal flora, and ameliorate physiological symptoms of DSSinduced colitis in mice via repressing TLR4/MyD88/NF-κB signal transduction [62]. In our study, DSS exposure elevated the levels of TLR4, MyD88, p-p65 and p-IκBα in colon tissues.…”
Section: Discussionsupporting
confidence: 54%
“…34 Abnormal activation of the TLR4/ MyD88/NF-κB signaling pathway in colonic mucosa of UC patients causes persistent aggravation of intestinal inflammation and becomes targets for drug therapy in UC patients. 35 The regulation of the TLR4/MyD88/NF-κB pathway by polyphenols has been reported previously. Xue et al have reported that EGCG, a constituent of tea polyphenols, mitigates DSS-induced colitis through the TLR4/MyD88/ NF-κB signaling pathway in rats.…”
Section: ■ Discussionmentioning
confidence: 65%
“…Toll-like receptors (TLRs) play a key role in nonspecific or innate immune defense, and activation of the TLR4/MyD88/NF-κB signaling pathway led to the expression of inflammatory factors, such as TNF-α and IL-1β . Abnormal activation of the TLR4/MyD88/NF-κB signaling pathway in colonic mucosa of UC patients causes persistent aggravation of intestinal inflammation and becomes targets for drug therapy in UC patients . The regulation of the TLR4/MyD88/NF-κB pathway by polyphenols has been reported previously.…”
Section: Discussionmentioning
confidence: 98%
“…NF-κB has been shown to be activated in UC, which can stimulate the secretion of multiple inflammatory cytokines to form an inflammatory cascade (26). Suppression of NF-κB was demonstrated to slow UC development (27), while activation was verified to promote UC progression (28). Previous literatures reported that some components of TQDD exerted excellent anti-inflammatory activity via regulating NF-κB pathway (29,30).…”
Section: Discussionmentioning
confidence: 99%